2007
DOI: 10.1071/mf07032
|View full text |Cite
|
Sign up to set email alerts
|

Validation of age and growth in a long-lived temperate reef fish using otolith structure, oxytetracycline and bomb radiocarbon methods

Abstract: Generating age estimates for long-lived fish requires particular attention to validation because they are usually difficult to age owing to narrow increment structure. A robust validation of the accuracy and precision of banded morwong, Cheilodactylus spectabilis, sampled from Tasmanian waters, was undertaken. Age at the first enumerated increment was established from analysis of juvenile cohorts, and the timing and periodicity of increment formation was established using a quantitative model from oxytetracycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
(59 reference statements)
0
24
0
1
Order By: Relevance
“…Conversely, there would be no obvious advantage for maturity to be delayed in N. macropterus and C. spectabilis because the growth curves of these species exhibit a marked tendency to level off very early in life (Fig. 9, Jordan 2001a;Ewing et al 2007) and thus any such delay would not result in a sufficient increase in reproductive output throughout the remainder of life to offset mortality.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, there would be no obvious advantage for maturity to be delayed in N. macropterus and C. spectabilis because the growth curves of these species exhibit a marked tendency to level off very early in life (Fig. 9, Jordan 2001a;Ewing et al 2007) and thus any such delay would not result in a sufficient increase in reproductive output throughout the remainder of life to offset mortality.…”
mentioning
confidence: 99%
“…4), it is helpful to consider the early and similar pattern of growth of the cheilodactylids N. macropterus and C. spectabilis, for both of which there were more extensive data (Jordan 2001a;Ewing et al 2007). Those studies showed that, by 1 year of age, N. macropterus and C. spectabilis had attained fork lengths of 145 and 132 mm, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its flexibility, not only can the model detect the high growth rate of longtail tuna and long-lived temperate reef fish (Ewing et al, 2007) during an early phase, but it can also discover the low growth rate of large temperate pelagic fish (Stewart et al, 2004). The five-parameter Schnute-Richards model (Schnute & Richards, 1990) can be expressed as…”
Section: Deterministic Growth Models 43mentioning
confidence: 99%